La liturgie céleste dans la peinture murale de Moldavie / The Heavenly Liturgy in Moldavian Mural Painting - Tereza Sinigalia (Anastasis: Research in Medieval Culture and Art, 2015)
The Divine Liturgy or The Heavenly or The Angelic Liturgy is a mystic theme with its roots in the commentaries of great Orthodox theologians from the 6th to 15th century and in direct links with the texts of Eucharistic Liturgy itself. There are few differences between iconographic redactions in the Balkan churches, where it is rarely represented, and in the Romanian Countries in the Middle Ages. We find the theme in Moldavian monastic churches from 16th century and the beginning of 17th, in circular compositions around the lower register of the drum of the tower upon the nave: St Nicholas church of Probota Monastery (1532 – 1534/1535); St George church of St John the New Monastery in Suceava /Metropolitan Bishopric Church of Moldavia of the time (1534); Resurrection church of Suceviţa Monastey (1601), Descent of the Holy Spirit of Dragomirna Monastery (after 1610). As concerning the presence of the theme on the eastern wall of the narthex in the Descent of the Holy Spirit church of Dobrovăţ Monastery, considered to be the first one redaction in Moldova, we think that the large composition represents the procession from the Vesper office of the Holy Friday, with the epithaphios with the image of Christ dead, combined with some elements from the Divine Liturgy.